Environmental Migrants and International Law - Alexander Shytov (CMU Journal of Law and Social Sciences Faculty Of Law Chaing Mai University, 2019)
This journal that publishes academic articles and research articles from both inside and outside the university. Published 6 months. No. 1 January - June NO. 2 July - December